Fatores de Governança em Sistemas-de-Sistemas: Análise de uma Instituição Pública Brasileira - Imamura, Marcio; Costa, Luiz Alexandre; Pereira, Bruno; Ferreira, Francisco Henrique; Fontão, Awdren; dos Santos, Rodrigo Pereira (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2020)
SoS is an approach that allows the offering of unique capabilities through the integration of existing systems. SoS approach can be observed in several domains such as military, logistics, transportation, healthcare etc. Despite the great interest in this field in the last years, many problems are still open. Since the systems that compose an SoS are independent and have individual objectives,one of the most critical challenges is enabling the governance of this class of system. Therefore, this paper presents an investigation on the factors that should be taken in consideration when implementing SoS governance. To do so, we carried out a survey with professionals of a Brazilian public organization.